2023
DOI: 10.1111/iju.15346
|View full text |Cite
|
Sign up to set email alerts
|

Differences in overall survival of penile cancer patients versus population‐based controls

Lukas Scheipner,
Stefano Tappero,
Mattia Luca Piccinelli
et al.

Abstract: PurposeTo assess whether 5‐year overall survival (OS) of squamous cell carcinoma of the penis (SCCP) patients differs from age‐matched male population‐based controls.MethodsWe relied on the Surveillance Epidemiology and End Results database (2004–2018) to identify newly diagnosed (2004–2013) SCCP patients. For each case, we simulated an age‐matched control (Monte Carlo simulation), relying on the Social Security Administration (SSA) Life Tables with 5 years of follow‐up. We compared OS between SCCP patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…1 Published data from national databases and clinical registries have highlighted significant gaps in the diagnosis and management of penile cancer due to geographical differences in its prevalence and survival patterns, and more studies are required to comprehensively analyze specific cancer epidemiology, modify underlying risk factors, and optimize on current treatment strategies. 2 In this large-scale study using the SEER database of penile cancer analyzing newly diagnosed patients between 2004 and 2013, 3 it was found that more than two-thirds of patients (79%) presented with lower-stage cancer (stages I and II). However, the 5-year overall survival showed a worsening trend with more advanced cancer compared with age-matched population-based controls (from a 17% difference in stage I to a 61% difference in stage IV) with corresponding higher cancer-specific mortality (CSM) over other-cause mortality (OCM), especially with more advanced stages of cancer (60% vs. 14% for stage IV patients).…”
mentioning
confidence: 98%
“…1 Published data from national databases and clinical registries have highlighted significant gaps in the diagnosis and management of penile cancer due to geographical differences in its prevalence and survival patterns, and more studies are required to comprehensively analyze specific cancer epidemiology, modify underlying risk factors, and optimize on current treatment strategies. 2 In this large-scale study using the SEER database of penile cancer analyzing newly diagnosed patients between 2004 and 2013, 3 it was found that more than two-thirds of patients (79%) presented with lower-stage cancer (stages I and II). However, the 5-year overall survival showed a worsening trend with more advanced cancer compared with age-matched population-based controls (from a 17% difference in stage I to a 61% difference in stage IV) with corresponding higher cancer-specific mortality (CSM) over other-cause mortality (OCM), especially with more advanced stages of cancer (60% vs. 14% for stage IV patients).…”
mentioning
confidence: 98%